Effects of Orlistat or Telmisartan on the Serum Free Fatty Acids in Non-alcoholic Fatty Liver Disease Patients: An Open-Labeled Randomized Controlled Study - Esmail, Vian Ahmed Wasta; Al-Nimer, Marwan S.M.; Mohammed, Mohammed Omer (Turkish Journal of Gastroenterology, 2022)
Background/Aims: One of the important inducers of inflammatory responses and accumulation of fat in hepatocytes is free fatty acids (FFA) that ultimately lead to the development of non-alcoholic fatty liver disease (NAFLD). Patients with NAFLD have high levels of plasma FFAs which is usually associated with type 2 diabetes and components of metabolic syndrome including dyslipidemia. To investigate the effects of orlistat (a lipase enzyme inhibitor) or telmisartan (an angiotensin receptor blocker) on the serum FFAs in NAFLD patients taking in consideration the baseline lipid profile.Materials and Methods: This open-label clinical trial was carried out in the Department of Pharmacology, College of Medicine at University of Sulaimani in cooperation with Shar Teaching Hospital in Sulaimani city-Kurdistan Region of Iraq. A total number of 74 NAFLD patients were recruited and grouped randomly into Group I (n=25) treated with orlistat (120 mg/day orally) for 12 weeks, Group II (n=24) treated with telmisartan (20 mg/day orally) for 8 weeks, and Group III (n=25) treated with placebo (carboxymethyl cellulose) once daily. Fasting serum level of FFA and lipid profile including total cholesterol, triglyceride, high-density lipoprotein and non-high-density lipoproteins were determined.Results: Orlistat and telmisartan significantly reduced the triglyceride-glucose index and free fatty acid levels (P ˂ 0.001) in patients with non-alcoholic fatty liver diseases.Conclusion: Short term treatment with orlistat or telmisartan, produce effective and significant reductions in FFAs in patients with NAFLD compared to placebo. Orlistat effectively reduces the free fatty acid irrespective to the baseline lipid profile.